Am nevoie de ajutor repede !!!
Anexe:
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
Explicație:
3a(√2 + √3) + b(√2 - √3) = 3a√2 + 3a√3 + b√2 - b√3
= √2(3a + b) + √3(3a - b)
√12 + √2 = 2√3 + √2
√3(3a - b) + √2(3a + b) = 2√3 + √2
3a - b = 2
3a + b = 1
b = 3a - 2
3a + 3a - 2 = 1
6a = 1 + 2 = 3
a = 3/6 = 1/2
b = 3/2 - 2 = 3/2 - 4/2 = -1/2
Alte întrebări interesante
Fizică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă